Camellias at a Glance - Sydney Park Brown (EDIS, 2012)
Native to Asia, the first camellia plants were brought to America in 1797 and grown in New England greenhouses. Over the last 200 years, they have proven to be dependable additions to the southern landscape, where they grow and bloom with minimal care in most inland areas of North and Central Florida. Camellias are long lived and function well as foundation plantings, screens, accent plants, background groupings, and hedges. Camellias flower in the fall and winter when few other plants are blooming. For the remainder of the year, their glossy, evergreen foliage, interesting forms and textures, relatively slow growth, and low maintenance make camellias excellent landscape plants worthy of more use. This revised 6-page fact sheet was written by Sydney Park Brown, and published by the UF Department of Environmental Horticulture, April 2012.